1980
DOI: 10.1007/bf00000950
|View full text |Cite
|
Sign up to set email alerts
|

Micropyle of some salmonins and coregonins

Abstract: SynopsisThe micropyle of seven salmonins and four coregonins were examined by a scanning electron microscope. In addition, the micropyle of Coregonus pidschian is described for the first time. The micropyles and the surface pattern may be used for identification of eggs. The studied micropyle belongs to two different types: 1. micropyle with flat pit and long canal (type 11) and 2. micropyle with canal but without pit (type 111). The sides of the micropyle canal are often reinforced by annular or helicoid thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

1981
1981
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
2
14
0
Order By: Relevance
“…The ultrastructure of the micropylar canals, as well as the diameters of the micropyles, were the most significant characters for distinguishing between E. malabaricus and E. coioides. This is also consistent with the observation that while the outer surface of the zona radiata may be useful for distinguishing among fishes from different families or orders, the ultrastructural features of the micropyle can serve as taxonomic characters that are species-specific (Riehl & Schulte, 1978;Riehl, 1980Riehl, , 1993.…”
Section: Discussionsupporting
confidence: 83%
“…The ultrastructure of the micropylar canals, as well as the diameters of the micropyles, were the most significant characters for distinguishing between E. malabaricus and E. coioides. This is also consistent with the observation that while the outer surface of the zona radiata may be useful for distinguishing among fishes from different families or orders, the ultrastructural features of the micropyle can serve as taxonomic characters that are species-specific (Riehl & Schulte, 1978;Riehl, 1980Riehl, , 1993.…”
Section: Discussionsupporting
confidence: 83%
“…During oogenesis glucose and amino acids are incorporated in developing oocytes via the follicular epithelium (Riehl, 1978;Nagahama, 1983;Guraya, 1986) (Nomura, 1964;Matsubara et al, 1985) and a positive influence on sperm motility was also discussed (Yoshida and Nomura, 1972 Oshiro and Hibiya, 1982;Berndtson and Goetz, 1990) and may be liberated during this process. They also occur in the multivesicular bodies of the oocytes (Sire et al, 1994 Riehl (1980) found the micropylar structure to be a species-specific characteristic in salmonid eggs.…”
Section: Organic Components Metabolitesmentioning
confidence: 97%
“…The micropyle and surface pattern of fish eggs are important characteristic criteria for identification of different teleosts (Riehl & Schulte 1978, Riehl 1980, Riehl & Koleoscha 1993, Chen et al 1999, Vorobyeva & Markov 1999, Breining & Britz 2000. Shape, number, size of micropyle and also reinforcement type in the micropyle canal; the diameter, number, and arrangement of the accessory openings; the modes of egg attachment to the substrate and the thickness of the membrane have been used for taxonomic purpose (Riehl 1993, Giulianini et al 1994, Chen et al 1999, Li et al 2000, Bless & Riehl 2002.…”
Section: Introductionmentioning
confidence: 99%